Quantitative carbon detector (QCD) for calibration-free, high-resolution characterization of complex mixtures. Issue 2 (11th November 2014) - Maduskar, Saurabh; Teixeira, Andrew R.; Paulsen, Alex D.; Krumm, Christoph; Mountziaris, T. J.; Fan, Wei; Dauenhauer, Paul J.
Abstract : A tandem catalytic microreactor for calibration-free quantification of complex mixtures. Abstract : Current research of complex chemical systems, including biomass pyrolysis, petroleum refining, and wastewater remediation requires analysis of large analyte mixtures (>100 compounds). Quantification of each carbon-containing analyte by existing methods (flame ionization detection) requires extensive identification and calibration. In this work, we describe an integrated microreactor system called the Quantitative Carbon Detector (QCD) for use with current gas chromatography techniques for calibration-free quantitation of analyte mixtures. Combined heating, catalytic combustion, methanation and gas co-reactant mixing within a single modular reactor fully converts all analytes to methane (>99.9%) within a thermodynamic operable regime. Residence time distribution of the QCD reveals negligible loss in chromatographic resolution consistent with fine separation of complex mixtures including cellulose pyrolysis products.